Storage Stability of Intermediate Moisture Cauliflower Brassica Oleracea, Var, Botrytis Cabbage Brassica Oleracea, Var, Capitata Using Radiation as Hurdle Technology - V, Sujatha; Chaturvedi, Anurag; K, Manjula (Journal of Food Technology Research, 2014)
Processing conditions were established for developing shelf stable ‘intermediate moisture’ (IM) cabbage and cauliflower. The new protocols were based on the hurdle technology (HT) - a mild heat treatment, addition of 1% Potassium meta bi sulphite as antimicrobial agent, partial dehydration to lower water activity (aw ) using two methods - Infrared drying (IR) and Tray drying (TD). The IM vegetables prepared were packed in 400 gauge polyethylene covers and treated with low doses of gamma radiation as major hurdle technologyand observed for shelf life stability at ambient conditions (30oC and 65% RH). The physical, chemical and pathological stability were monitored during storage. Infra-red dried (IR) vegetables treated with gamma radiation at 0.75-1.0 kGyyielded a product with improved rehydration potential, appearance and maximum nutrient retention up to 43.1%-44.6 % of vitamin C with maximum shelf life of 5 to 7 months.No significant changes were noticed in scores for color, taste, flavor, texture and overall acceptability during storage period. The growth of microbes were controlled throughout the study resulting in shelf stable IM vegetables. Among the four treatments studied, infrared dried with radiation dose of 0.75 kGy for cauliflower and1.0 kGy for cabbage was found to be best in obtaining high quality IM products with optimum sensory, microbial, nutritional quality and storability.